Benefits and risks of off label use of antipsychotics in insomnia and anxiety – APSY Oulu project. (31st December 2021) - Jääskeläinen, Erika; Haapea, Marianne; Juola, Teija; Rannikko, Irina; Rautio, Nina; Lehto, Sini; Ylitalo, Julia; Koponen, Hannu; Isohanni, Matti; Murray, Graham; Jones, Peter; Penttilä, Matti; et al.
Abstract: Background: Use of antipsychotics (APs) has increased in Europe. Main reason for this is off label use, most commonly the use of quetiapine for insomnia and anxiety. However, there is lack of studies analysing benefits and harms of APs in these conditions. APs have shown efficacy in the treatment of anxiety, but long term follow-ups are rare. Only two trials on effects of quetiapine in primary insomnia exist. Even small doses of APs may cause side-effects, such as increased weight, metabolic changes, and daytime drowsiness, but studies on small dose of APs are very few. The aim of the APSY Oulu project (https://www.oulu.fi/ltk/apsyoulu ) is to study the benefits and risks of APs in off label use. Methods: APSY Oulu project includes clinical patient data, questionnaire on physicians on APs off label prescriptions and systematic literature reviews on the topic. Results: In 2019–2020, we have collected pilot sample of 10 individuals starting quetiapine for insomnia, followed up for 12 months. They all had severe or very severe symptoms of insomnia, and used very small dose of quetiapine (mostly 12.5–25 mg). Four of them used quetiapine still at the 12 months follow-up, and their insomnia symptoms decreased during the follow-up. Side effects were common (e.g. increase heart rate, drowsiness). Based on questionnaire for Finnish physicians, APs off label prescriptions are mostly for insomnia and anxiety, most common drug being quetiapine. There is a need for guideline on monitoring the patients. Conclusions: Further studies on APs off label use and its safety are needed.